Identification of Lipid Markers of Plasmopara viticola Infection in Grapevine Using a Non-targeted Metabolomic Approach - Negrel, Lise; Halter, David; Wiedemann-Merdinoglu, Sabine; Rustenholz, Camille; Merdinoglu, Didier; Hugueney, Philippe; Baltenweck, Raymonde (Frontiers in Plant Science, 2018)
The Oomycete Plasmopara viticola is responsible for downy mildew, which is one of the most damaging grapevine diseases. Due to the strictly biotrophic way of life of P. viticola, its metabolome is relatively poorly characterized. In this work, we have used a mass spectrometry-based non-targeted metabolomic approach to identify potential Plasmopara-specific metabolites. This has led to the characterization and structural elucidation of compounds belonging to three families of atypical lipids, which are not detected in healthy grapevine tissues. These lipids include ceramides and derivatives of arachidonic and eicosapentaenoic acid, most of which had not been previously described in Oomycetes. Furthermore, we show that these lipids can be detected in Plasmopara-infected tissues at very early stages of the infection process, long before the appearance the first visible symptoms of the disease. Therefore, the potential use of these specific lipids as markers to monitor the development of P. viticola is discussed.